Comparative evaluation of animal manures and levels of applications on the growth performance of Diospyros mespiliformis Hochst ex A. Rich seed-lings - Lucky Wakawa; Ibrahim Musa; Aminu Abdulhamid; Alex Amininim (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Diospyros mespiliformis which is commonly known as African ebony is a valuable fruit tree species with important medicinal and nutritional values. The tree has a slow growth rate that discourages its propagation and at present attempts made towards improving its growth performance are scanty. This study, therefore, evaluates the effect of the type and quantity of animal manure on the growth performance of Diospyros mespiliformis to determine the suitable type of manure and quantity of application that will improve its growth performance.Method Poultry, cow, and goat manures were applied to Diospyros mespiliformis seedlings at 0 g (control), 15 g (10 t/ha-1), 30 g (25 t/ha-1), and 40 g (35 t/ha-1) in pots. The experiment was arranged in a 4 x 3 factorial in a completely randomized design with five (5) replicates.Results Type of manure had a significant effect on seedlings' stem height growth. The highest stem height growth of 11.64±1.54 cm was recorded by seedlings that received goat manure. The collar diameter and the number of leaves produced were not significantly affected by the type of manure. The Quantity of manure applied did not significantly affect stem height and collar diameter increment; however, it significantly affected the number of leaves produced. Application of 40 g of manures improved leaf production in Diospyros mespiliformis seedlings.Conclusion Application of animal manures improved the growth performance of Diospyros mespiliformis, however, seedlings that received goat manure had better growth performance.